Perancangan Mekanisme Pengaduk Kompos Sampah Organik dengan CAD/CAE - Budi Basuki; Andhi Akhmad Ismail; Sugiyanto; Dani Anggoro Hasan; Muhammad Alif (Proklamasi 45 University, 2024)
The management of organic waste into compost is one of the important solutions in an effort to reduce the negative impact of organic waste on the environment. A compost mixer is one of the technologies that can be used to speed up the process of decomposing and forming compost from organic waste. This research aims to continue previous research that has succeeded in making organic waste shredding machines. The methods used in this study include a literature survey on the basic principles in organic waste management, available technologies, and the design of stirring machine mechanisms that have been carried out previously. Based on the literature analysis, some factors in the design of the compost mixer machine are the material and shape of the composting blade, adequate construction strength, the need for sufficient rotation to achieve organic waste homogenization, and the ease of operation and maintenance. The design process utilizes CAD/CAE software to compile 3D models and simulate various operational conditions. The result of this research is the design of an efficient compost mixing machine mechanism. In addition, special attention is paid to the selection of materials and the shape of the stirring blades that are resistant to wear and corrosion. This design also takes into account the ease of access for routine cleaning and maintenance.